The effect of pregabalin and s-ketamine in total knee arthroplasty patients: A randomized trial - Lajla Kadic; Frank G van Haren; Oliver Wilder-Smith; Jorgen Bruhn; Jacques J Driessen; Maarten C de Waal Malefijt (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Pain reduction is important for rehabilitation after total knee arthroplasty. Intra- and peri-articular infiltration with local anesthetics may be an alternative to commonly used locoregional techniques. Adding pregabalin orally and s-ketamine intravenously may further reduce postoperative pain. Material and Methods: This prospective, randomized, double-blind, placebo-controlled study compared two methods of perioperative analgesia. Control patients received a standardized multimodal postoperative analgesic regime of paracetamol, diclofenac, and piritramide-patient-controlled analgesia, including ropivacaine knee infiltration during surgery. The study group received pregabalin orally and s-ketamine intravenously as an additional medication to the standard multimodal regimen. The control group received placebo. Results: The study group showed lower piritramide consumption during the first 24 h (P: 0.043), but with more side effects such as diplopia and dizziness. Conclusion: Addition of pregabalin and s-ketamine resulted in lower piritramide consumption during the first 24 h postoperatively. However, more investigation on benefits versus side effects of this medication is required.